Synthesis, Characterization and Magnetic properties of Nanoparticles of Cobalt Doped Ferrite - Gupta, Priyanka; Vijai, Dr. Ravi Kumar; Chander, Subhash (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2022)
Ferrites are ceramic like material having magnetic properties which are being utilized for several applications. Cobalt ferrites are hard magnetic material with high coercivity. In our study Crystalline, Magnetic nanoparticles of Cobalt ferrite Co0.8Fe2.2O4 were synthesized by Sol Gel Method using ferric chloride and cobalt nitrate with NaOH as a reactant. Structural characteristics of samples were determined by X-Ray diffraction, FESEM and TEM. Particle size found 14.26nm by using Debye Scherrer method. Scanning electron microscopic (SEM) studies revealed nano-crystalline nature of the sample. AFM showed surface roughness. Magnetic properties were investigated using VSM (vibrating sample magnetometer). Various magnetic parameters such as saturation magnetization (Ms) and remanence (Mr) and coercivity (Hc) are obtained from the hysteresis loops. The calculated value of saturation magnetization in our study for Cobalt ferrite was found lower than the value reported for the bulk. The coercivity was found very high which indicate that the nanoparticles exhibit ferromagnetic behavior.